Islamic Peace Ethics : Legitimate and Illegitimate Violence in Contemporary Islamic Thought - Shadi, Heydar; Shadi, Heydar (Baden-Baden Nomos Verlagsgesellschaft mbH & Co. KG)
Proceedings of the International Workshop (3z(BIslamic Peace Ethics: Legitimate and Illegitimate Violence in Contemporary Islamic Thought(3y(B, organized 15-17 October 2015 by the Institute for Theology and Peace (ithf), Hamburg. More than 20 researchers from different countries including Indonesia, Pakistan, Iran, Germany, UK, USA, and Belgium discussed the peace and war in contemporary Islamic thought from different disciplines such as theology, philosophy, religious studies, cultural studies, and political sciences.s
English
Keywords: Political ideologies; Political Science; Ethics; Hadith; Islam; Jihad; Muslims; Quran